Pembangunan Tempat Posyandu Pada Dusun IV Desa Sei Sijenggi, Kecamatan Perbaungan, Kabupaten Serdang Bedagai, Sumatera Utara - Rhini Wulan Dary; Muhammad Ari Subhan Harahap; Citra Utami; Tetra Oktaviani; Dina Tri Septiningtiyas (Politeknik Piksi Ganesha Indonesia, 2025)
Posyandu (Integrated Health Service Post) is a government program in Indonesia that provides healthcare services and child development support at the community level. In Dusun IV, Sei Sijenggi Village, Perbaungan Subdistrict, Serdang Bedagai Regency, North Sumatra, a permanent Posyandu facility will be constructed on a 3x3 meter plot located in the yard of the Posyandu head’s residence. This location is approximately 49.4 km from Politeknik Negeri Medan. The establishment of this facility aims to improve access to routine monthly health check-ups for mothers and children, serve as a venue for community activities such as health education and socialization, and eliminate miscommunication caused by the previous relocation of the Posyandu site. The building will feature isolated footings at all four corners, ceramic flooring, and a roof structure made of wooden trusses and zinc sheeting. This initiative also supports the government's program to enhance the welfare and health of the local community.